Investigation of filler effects on the compounding of freeze-dried orodispersible tablets containing Annona muricata extract - Noor Azman, Syahiera Ezzah; Abd Razak, Fashli Syafiq; Wan Kamal, Wan Hamirul Bahrin; Gan, Kok Zheng; Long, Chiau Ming; Helal Uddin, A.B.M.; Sarker, Md. Zaidul Islam; Liew, Kai Bin (International Journal of Pharmaceutical Compounding, Inc., 2020)
Orally disintegrating tablets are a solid dosage form that will disintegrate rapidly within 3 minutes upon contact with saliva. Fillers or diluents are excipients that are used to make up the volume of orally disintegrating tablets, and some might act as a disintegrant or binder that will affect the physical properties of orally disintegrating tablets. The objective of this study was to formulate and evaluate physical properties of orally disin- tegrating tablets containing Annona muricata leaves extract by a freeze- drying method using different fillers at different concentrations. In this study, fifteen formulations of orally disintegrating tablets were prepared by a freeze-drying method with different fillers such as starch, lactose, microcrystalline cellulose, StarLac, and CombiLac at 5%, 10%, and 15%. The orally disintegrating tablets were evaluated for hardness, thickness, weight variation, friability, and disintegration time test. The optimum formulation was chosen and incorporated with Annona muricata leaves extract. The results obtained in this work indicated that Formulation 3, with 15% starch, was the most optimum formulation due to the shortest disintegration time (21.08 seconds ± 4.24 seconds), and all the physical tests were within the acceptable range. The orally disintegrating tablets containing Annona muricata leaves extract possessed antioxidant activity and stable at least for 3 months under 60°C and 75% RH.